KULTIVASI DAN EKSTRAKSI MINYAK DARI MIKROALGA Botryococcus braunii DAN Nannochloropsis sp. - musdalifah, Musdalifah; Rustam, Yoswita; Amini, Sri (LPPM Universitas Negeri Jakarta, 2015)
AbstractMicroalgae has high content of vegetable oil. The extraction of microalgae oil can be more efficient with the cell wall destruction, it was aimed to freeing oil that locked inside the cells and be soluble in organic solvent (n-hexane). The study aimed to determined the microalgae growth, the influence of different pH and different species of microalgae with extraction using microwave on oil production by Botryococcus braunii and Nannochloropsis sp. Experimental method with the randomized design was used in this study. The cultivation was performed until the stationery phase is reached so that the biomass can be harvested for oil extraction. The oil compound analysis is conducted using GC-FID. The data in this study has been tested by SPSS 16.0 with t-test and anova two ways. The statistic result showed that there is no differences in cell density of Botryococcus braunii and Nannochloropsis sp. (p= 0,163), likewise with there is no differences in amount of oil extract by Botryococcus braunii and Nannochloropsis sp. (p= 0,323). However, different results are pH treatment influencing oil extraction result (p= 0,006).Composition of fatty acid in Nannochloropsis sp. was dominated by saturated fatty acids, while the fatty acid composition of Botryococcus braunii was equal between saturated an unsaturated fatty acid. Keywords: Botryococcus braunii, cultivation, extraction, growth, microalgae, Nannochloropsis sp., oil, pH.